Preoperative Serum C-Reactive Protein Levels and Post-Operative Lymph Node Ratio Are Important Predictors of Survival After Pancreaticoduodenectomy for Pancreatic Ductal Adenocarcinoma - Sanjay, Pandanaboyana; Leaver, Heather; de Figueiredo, Rodrigo S; Ogston, Simon; Kulli, Christoph; Polignano, Francesco M; Tait, Is (JOP. Journal of the Pancreas, 2012)
<!--[if gte mso 9]> Normal 0 14 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Tabella normale"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; mso-ansi-language:#0400; mso-fareast-language:#0400; mso-bidi-language:#0400;} --> <!--[endif] --> Context There is paucity of data on the prognostic value of pre-operative inflammatory response and post-operative lymph node ratio on patient survival after pancreatic-head resection for pancreatic ductal adenocarcinoma. Objectives To evaluate the role of the preoperative inflammatory response and postoperative pathology criteria to identify predictive and/or prognostic variables for pancreatic ductal adenocarcinoma. Design All patients who underwent pancreaticoduodenectomy for pancreatic ductal adenocarcinoma between 2002 and 2008 were reviewed retrospectively. The following impacts on patient survival were assessed: i) preoperative serum CRP levels, white cell count, neutrophil count, neutrophil/lymphocyte ratio, lymphocyte count, platelet/lymphocyte ratio; and ii) post-operative pathology criteria including lymph node status and lymph node ratio. Results Fifty-one patients underwent potentially curative resection for pancreatic ductal adenocarcinoma during the study period. An elevated preoperative CRP level (greater than 3 mg/L) was found to be a significant adverse prognostic factor (P=0.015) predicting a poor survival, whereas white cell count (P=0.278), neutrophil count (P=0.850), neutrophil/lymphocyte ratio (P=0.272), platelet/lymphocyte ratio (P=0.532) and lymphocyte count (P=0.721) were not significant prognosticators at univariate analysis. Presence of metastatic lymph nodes did not adversely affect survival (P=0.050), however a raised lymph node ratio predicted poor survival at univariate analysis (P<0.001). The preoperative serum CRP level retained significance at multivariate analysis (P=0.011), together with lymph node ratio (P<0.001) and tumour size (greater than 2 cm; P=0.008). Conclusion A pre-operative elevated serum CRP level and raised post-operative lymph node ratio represent significant independent prognostic factors that predict poor prognosis in patients undergoing curative resection for pancreatic ductal adenocarcinoma. There is potential for future neo-adjuvant and adjuvant treatment strategies in pancreatic cancer to be tailored based on preoperative and postoperative factors that predict a poor survival.